Articulation of Indonesian Identity in Mahabharata Epic Puppet Comics by Sundanese, Javanese, and Balinese Comic Artists - I Wayan Nuriarta; I Nyoman Suarka; Ida Ayu Laksmita Sari; Suryadi Suryadi (Jurnal Kajian Bali (Journal of Bali Studies), 2024)
This research examines Mahabharata epic puppet (wayang) comics, created by three renowned comic artists: R. A. Kosasih, Teguh Santosa, and Gun Gun, who respectively have Sundanese, Javanese, and Balinese cultural backgrounds, through the lens of Indonesian identity articulation. The comics of wayang which translates ‘puppet’, are a distinctive genre that employs panels to depict puppetry tales. While being influenced by foreign cultures such as American comic art and the Indian Mahabharata epic, these artists intentionally incorporate Indonesian elements into their works. This is evident from 1955 to the present. This research used a critical qualitative descriptive approach to investigate the articulation of the identity discourse within the cultural realm of comics. The comic works of the artists are analysed through articulation and hegemony theory. The research concludes that the artists’ works establish a cultural connection and relate cultural comic art to Indonesian readers. This not only constructs Indonesian identity but also promotes cultural diversity.